2008
DOI: 10.1177/1933719107311783
|View full text |Cite
|
Sign up to set email alerts
|

Regional Expression of Aquaporin 1, 4, and 9 in the Brain During Pregnancy

Abstract: Pregnancy is a state of physiologic adaptation, with significant changes in cardiovascular, renal, and hemodynamic systems. Aquaporins (AQPs) may play a role in facilitating these changes. While AQP expression has been assessed in several organs during pregnancy, little is known about its expression in the brain during pregnancy. Therefore, this study assesses the regional expression of AQP1, 4, and 9 during pregnancy and the postpartum period using real-time quantitative polymerase chain reaction. The authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
6
7
0
Order By: Relevance
“…AQP9 labelling has previously been reported in astrocytes in the periventricular parenchyma and glia limitans, in endothelial cells at the border of the subarachnoid space, and in neurons, particularly catecholaminergic neurons (Li et al 2005;Wiegman et al 2008). The current study showed that AQP9 was expressed in astrocytes and neurons after pMCAO.…”
Section: Discussionsupporting
confidence: 74%
“…AQP9 labelling has previously been reported in astrocytes in the periventricular parenchyma and glia limitans, in endothelial cells at the border of the subarachnoid space, and in neurons, particularly catecholaminergic neurons (Li et al 2005;Wiegman et al 2008). The current study showed that AQP9 was expressed in astrocytes and neurons after pMCAO.…”
Section: Discussionsupporting
confidence: 74%
“…9498 Interestingly, AQP4 is increased in the brain during pregnancy. 99 100 . The effect of increased expression of AQP4 in the brain during pregnancy is not clear, but could affect seizure threshold as AQP4 knockout mice were shown to be less susceptible to seizure, suggesting elevated AQP4 lowers the seizure threshold.…”
Section: Mechanisms Of Seizure During Preeclampsiamentioning
confidence: 99%
“…Among this family of water channels, aquaporin 9 demonstrates the greatest homology to aquaporins 3 and 7, and the least molecular likeness to aquaporin 1 [31]. As well as being expressed in organs such as the human liver [31], brain [32], osteoclast cells [34], Figure 1. Box and whisker plot of aquaporin 9 mRNA expression in chorioamniotic membranes from women at term.…”
Section: What Is Aquaporin 9?mentioning
confidence: 99%
“…In a series of investigations using a rat model, Lindsay and Murphy [61] have reported a role for aquaporins in luminal fluid changes. Aquaporin 9 was localized to the apical glandular epithelium with increased immunofluorescent staining after implantation and the authors suggest its role in the re-absorption of glandular contents; and (3) recently, in an animal model, Wiegman et al [32] described the differential and regional expression of aquaporin 9 in the rat brain during pregnancy. The authors found that aquaporin 9 distribution did not differ between the pregnant and the non-pregnant state, but that its expression decreased in the posterior cerebrum when comparing non-pregnant and latepregnancy animals, and in the cerebellum in both mid-pregnant and late-pregnant rats compared with non-pregnant animals.…”
Section: Normal Pregnancy and Aquaporinmentioning
confidence: 99%
See 1 more Smart Citation